ISSUES OF THE JUDICIAL AND EDUCATIONAL SYSTEMS MODERNISATION IN POST-REFORM RUSSIA IN “RUSSKIYE VEDOMOSTI” NEWSPAPER IN 1870s - Taimasova, Yanina V. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2017)
The activities of the liberal newspaper “Russkiye Vedomosti” were mainly focused on the struggle for social modernization of Russia and implementation of the liberal reforms of the 1860-1870s. The newspaper actively defended the liberal principles for the implementation of the judicial reform and the education system. The editorial staff members were well-known liberal scholars N.S.Skvortsov, A.I. Chuprov, A. Postnikov, and others. N.S. Skvortsov’s “liberal team” believed that it was necessary to consistently implement the Judicial statutes of 1864 and develop the jury system. “Russkiye Vedomosti” was opposed to the idea of “people’s trial”, proposed by M.N. Katkov. The lack of lawyers hampered the development of the legal profession, so the newspaper made a project on the involvement of lawyers and their assistants. The newspaper consistently defended the principles of the Charter of 1863, it supported the autonomy of universities. “Russkiye Vedomosti” informed in detail its readers of the conﬂict of liberal professors Dmitriev and Chicherin with the leadership of the Moscow University. The newspaper actively campaigned for the prison reform. The liberal paper’s staff believed that the main obstacle to the development of the judicial - legal system was the cultural backward-ness of the country and the despotic form of government. The newspaper actively defended freedom of expression. Liberal commentators denounced revolutionary terror, because it violated the law and the right, but the political sympathies of the newspaper were on the side of the students.